Case report: Identification of acute promyelocytic leukemia during osimertinib resistance followed by granulocyte colony-stimulating factor and pembrolizumab - Tian, Huohuan; Yang, Linhui; Hou, Wang; Wu, Yu; Dai, Yang; Yu, Jiang; Liu, Dan (Frontiers in Oncology, 2023)
Background The occurrence of acute promyelocytic leukemia (APL) during management of lung cancer is rare and life-threatening. It was mainly reported to be secondary to chemoradiotherapy. Few studies reported an increased incidence of therapy-related acute promyelocytic leukemia (t-APL), or after gefitinib available. Case presentation We reported a patient suffered from thrombocytopenia after oral Osimertinib in combination with intensive modulated radiotherapy (IMRT). She showed an unrecoverable low platelet count for half a year, which progressed to concomitant leukopenia, and transient appearance of orthochromatic normoblasts in the peripheral blood test, indicating a dormant myeloid disorder. Owing to simultaneous resistance of epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI), pembrolizumab and granulocyte colony-stimulating factor (G-CSF) were administered, unveiling prominent signs of hematological malignancy in peripheral blood test which was later identified as t-APL. Conclusion In general, patients undergoing EGFR-TKI combined with local radiotherapy should be concerned about hematological assessment. If patients exhibit unrecoverable abnormality in routine blood examination, secondary non-solid malignancy other than myelosuppression should be considered and further lung cancer treatment should be suspended.